2006
DOI: 10.1002/ijc.22090
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cyanidin‐3‐glucoside and an anthocyanin mixture from bilberry on adenoma development in the ApcMin mouse model of intestinal carcinogenesis—Relationship with tissue anthocyanin levels

Abstract: Anthocyanins are dietary flavonoids, which can prevent carcinogen-induced colorectal cancer in rats. Here, the hypotheses were tested that Mirtoselect, an anthocyanin mixture from bilberry, or isolated cyanidin-3-glucoside (C3G), the most abundant anthocyanin in diet, interfere with intestinal adenoma formation in the Apc Min mouse, a genetic model of human familial adenomatous polyposis, and that consumption of C3G or Mirtoselect generates measurable levels of anthocyanins in the murine biophase. Apc Min mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
111
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 27 publications
9
111
1
1
Order By: Relevance
“…These components include saponins (24)(25)(26); monosaccharides, disaccharides, and oligosaccharides (27); and the phenolic components ferulic acid (28,29), p-coumaric acid (30), kaempferol (31), phytate (32,33), and at smaller concentrations, catechins (34), anthocyanidins (35), and isoflavonoids (36). All of these components are primarily in aqueous-alcohol extracts of dry beans (37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…These components include saponins (24)(25)(26); monosaccharides, disaccharides, and oligosaccharides (27); and the phenolic components ferulic acid (28,29), p-coumaric acid (30), kaempferol (31), phytate (32,33), and at smaller concentrations, catechins (34), anthocyanidins (35), and isoflavonoids (36). All of these components are primarily in aqueous-alcohol extracts of dry beans (37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of absolute dose of agent, cyanidin-3-glucoside was less efficacious than the Mirtoselect mixture. Furthermore, authors suggested that different results obtained, in comparison with other studies (Kang et al, 2003) were possibly due in part to the higher dose of anthocyanins employed but also due to the different way of administration since anthocyanins tend to be unstable in aqueous solution at neutral pH (Cooke et al, 2006). Recently, bilberry [(BB),Vaccinium myrtillus], lingonberry (LB, Vaccinium vitis-idaea), and cloudberry (CB, Rubus chamaemorus), rich in anthocyanins, proanthocyanidins and ellagic acid respectively, proved to be chemopreventive as demonstrated by a significant reduction in the number of intestinal tumors in Min/1 mice.…”
Section: Cytotoxicity In Colon and Other Cancer Cell Linesmentioning
confidence: 82%
“…Anthocyanin-rich berry extracts protected against esophageal cancer in rodents (6) and reduced adenoma development in Apc Min mice (7), a model of human familial adenomatous polyposis coli. Mirtocyan and cyanidin-3-glucoside as a single agent were also efficacious in the Apc Min model (8). Additionally, cyanidin-3-glucoside interfered with experimental skin tumorigenesis and reduced lung tumor growth and metastasis in the A549 nude mouse xenograft model (22).…”
Section: Discussionmentioning
confidence: 98%
“…18), which reduced adenoma number by 30% (8). The last third of the daily dose was administered in the early morning before surgery, when the patients were fasting.…”
Section: Intervention and Dosementioning
confidence: 99%
See 1 more Smart Citation